Altruistic eWOM marketing: More than an alternative to monetary incentives. (July 2016) - Reimer, Thomas; Benkenstein, Martin
Abstract: As a form of word of mouth, online reviews are used to reduce uncertainty about service quality and direct consumer attitudes and behavior. As a consequence of the high persuasiveness and the broad accessibility of electronic word of mouth (eWOM), companies are very interested to proactively managing this form of customer-to-customer communication. Compared with traditional advertising provides, eWOM marketing is a more credible and low-cost alternative. So far marketers have commonly used monetary incentives to influence customer-to-customer communication. However, this form also includes potential negative consequences such as credibility loss through consumer skepticism and crowding-out effects. This study analyzed two new incentive programs for increasing recommendation likelihood that considered the activation of an altruistic form of motivation to overcome these drawbacks. Therefore, an experiment was designed with three experimental groups (incentive programs) vs. a control group (no incentive). Finally, the results are discussed while taking into account the advantages and drawbacks of the particular incentive program to deduce practical implications.